2022
DOI: 10.3390/cimb44080228
|View full text |Cite
|
Sign up to set email alerts
|

Daphne odora Exerts Depigmenting Effects via Inhibiting CREB/MITF and Activating AKT/ERK-Signaling Pathways

Abstract: Daphne odora, a blooming shrub, has been traditionally used for various medicinal purposes. However, information on its anti-melanogenic activity and dermal application is limited. In this study, the Daphne odora extract (DOE), with constituents including daphnetin, was used to investigate depigmenting activity and the underlying mechanism of Daphne odora. DOE inhibited in vitro and cellular tyrosinase activity in a dose-dependent manner, and reduced the α-MSH-induced melanin biosynthesis to a control level. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…Mitogen-activated protein kinases (MAPKs), including extracellular signal-regulated kinase (ERK), p38 and c-Jun N-terminal kinase (JNK), are deeply involved in melanogenesis. In particular, ERK, through its phosphorylation, is responsible for regulating MITF protein stability, i.e., the phosphorylation of MITF decreases its stability and leads to its degradation in proteasomes, and ERK dephosphorylation paradoxically interrupts MITF degradation, thereby activating melanogenesis [ 35 , 36 , 37 ]. Therefore, we next sought to examine whether imperatorin regulates MITF activity via a MAPK pathway.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitogen-activated protein kinases (MAPKs), including extracellular signal-regulated kinase (ERK), p38 and c-Jun N-terminal kinase (JNK), are deeply involved in melanogenesis. In particular, ERK, through its phosphorylation, is responsible for regulating MITF protein stability, i.e., the phosphorylation of MITF decreases its stability and leads to its degradation in proteasomes, and ERK dephosphorylation paradoxically interrupts MITF degradation, thereby activating melanogenesis [ 35 , 36 , 37 ]. Therefore, we next sought to examine whether imperatorin regulates MITF activity via a MAPK pathway.…”
Section: Resultsmentioning
confidence: 99%
“…The activation of ERK is associated with a reduction in MITF degradation and pigmentation, while the inhibition of ERK increases melanin synthesis. Thus, MAPK signals in melanocytes are promising targets for the development of cosmetics and treatments for skin pigmentation through which MITF expression and stability can be increased [ 35 , 36 , 37 ]. Therefore, we evaluated the effectiveness of imperatorin for the inhibition of the ERK signaling pathway to further explore the molecular mechanisms of melanin synthesis in B16F10 cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, p38 phosphorylation was downregulated, and ERK phosphorylation was increased in the presence of Q3G. Although there are some controversial reports where ERK activation was shown to be increased in parallel with melanin synthesis [ 44 ], most of the studies reported that the phosphorylation of MITF with ERK1/2 led to its ubiquitination and consequent degradation, which resulted in suppressed melanogenesis [ 11 , 12 , 45 ]. The current results confirmed these reports where Q3G treatment elevated ERK phosphorylation.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that the activation of the Akt signaling pathway contributes to the inhibition of melanogenesis. 63 Intracellular cAMP inhibits phosphatidylinositol 3-kinase (PI3K) and stimulates GSK3β activity, subsequently controlling MITF expression. Activation of GSK3β phosphorylates MITF, thereby enhancing transcriptional activation of tyrosinase-related genes and melanogenesis.…”
mentioning
confidence: 99%